Necrology to Karol Jakubowicz - English edition, Journalism research (Žurnalistikos tyrimai, 2011)
On behalf of ECREAClaudia AlvaresPresidentOn behalf of Vilnius UniversityFaculty of CommunicationAndrius VaišnysDean